Are Employees Satisfied with New Normal? Study Of Health Protocol and Leadership Commitments on Aviation - Agung Wahyu Wicaksono; Isti Fadah; Ake Wihadanto (Universitas Medan Area, 2022)
Employee job satisfaction is disrupted during a pandemic, there are many concerns about being infected at work. The implementation of health protocols has been carried out as a new culture (new normal) to reduce the transmission rate in the workplace. This application is also accompanied by leadership commitment as a form of leadership responsibility in times of crisis. This study aimed to determine the relationship between health protocols, leadership commitment, and employee job satisfaction during a pandemic. The research was conducted using a quantitative method with PLS-SEM analysis by using SmartPLS 3. The number of research samples as many as 96 people conducted at Banyuwangi International Airport. The results showed that the health protocol had no effect on job satisfaction but had an influence on leadership commitment, while leadership commitment influences job satisfaction, at the same time the leadership commitment has succeeded in fully mediating the relationship between the health protocol and job satisfaction. This study tries to reveal a new variable in quantitative research: Health Protocol, which has been often referred to by Indonesian people for two years. We try to find the relationship with job satisfaction through leadership commitment.